Role for the Related Poly(ADP-Ribose) Polymerases Tankyrase 1 and 2 at Human Telomeres - Cook, Brandoch D. (American Society for Microbiology, 2002)
Telomere maintenance is essential for the continuous growth of tumor cells. In most human tumors telomeres are maintained by telomerase, a specialized reverse transcriptase. Tankyrase 1, a human telomeric poly(ADP-ribose) polymerase (PARP), positively regulates telomere length through its interaction with TRF1, a telomeric DNA-binding protein. Tankyrase 1 ADP-ribosylates TRF1, inhibiting its binding to telomeric DNA. Overexpression of tankyrase 1 in the nucleus promotes telomere elongation, suggesting that tankyrase 1 regulates access of telomerase to the telomeric complex. The recent identification of a closely related homolog of tankyrase 1, tankyrase 2, opens the possibility for a second PARP at telomeres. We therefore sought to establish the role of tankyrase 1 at telomeres and to determine if tankyrase 2 might have a telomeric function. We show that endogenous tankyrase 1 is a component of the human telomeric complex. We demonstrate that telomere elongation by tankyrase 1 requires the catalytic activity of the PARP domain and does not occur in telomerase-negative primary human cells. To investigate a potential role for tankyrase 2 at telomeres, recombinant tankyrase 2 was subjected to an in vitro PARP assay. Tankyrase 2 poly(ADP-ribosyl)ated itself and TRF1. Overexpression of tankyrase 2 in the nucleus released endogenous TRF1 from telomeres. These findings establish tankyrase 2 as a bona fide PARP, with itself and TRF1 as acceptors of ADP-ribosylation, and suggest the possibility of a role for tankyrase 2 at telomeres.